Sustainable Tourism Management - Swarbrooke, John (CABI Pub, 1998)
Sustainable tourism is attracting enormous attention today throughout the world. This book provides an up-to-date, comprehensive coverage of the practice and management of the subject. It offers a range of definitions of sustainable tourism from different sectors of tourism and different parts of the world. Key issues and current debates.